1994
DOI: 10.1002/hed.2880160506
|View full text |Cite
|
Sign up to set email alerts
|

4NQO carcinogenesis: A mouse model of oral cavity squamous cell carcinoma

Abstract: 4NQO reliably produced preneoplastic and malignant oral cavity lesions, which morphologically and histologically mimic human head and neck cancer. Lesions develop long after 4NQO exposure and without an inflammatory response. Thus, the model should be useful for molecular analysis of neoplastic transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 14 publications
(1 reference statement)
7
101
0
Order By: Relevance
“…Treatment of mouse oral epithelia with 4-nitroquinoline-1-oxide (4NQO) is a well-established model for human head and neck SCCs (20,21). The developing tumors are moderate to welldifferentiated SCCs that morphologically resemble human tumors (19). We found that p53 transgenic mice are highly susceptible to 4NQO-induced oral cancer and that the resulting tumors are more likely to progress.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Treatment of mouse oral epithelia with 4-nitroquinoline-1-oxide (4NQO) is a well-established model for human head and neck SCCs (20,21). The developing tumors are moderate to welldifferentiated SCCs that morphologically resemble human tumors (19). We found that p53 transgenic mice are highly susceptible to 4NQO-induced oral cancer and that the resulting tumors are more likely to progress.…”
Section: Introductionmentioning
confidence: 74%
“…Mutation in the p53 gene is also commonly seen in SCCs of oral mucosa (13)(14)(15)(16). Abnormal staining of p53 protein is a frequent finding (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…47 Among them, the 4-NQO-induced oral cancer mouse model is one of the most widely used, 24,25,47,48 as it recapitulates many features observed in human OSCC development including molecular expression of keratin, p16, and epidermal growth factor receptor (EGFR) which are associated with human oral carcinogenesis. Therefore, this model is suitable for the analysis of the OCC development in various mutant and transgenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 This model was selected because of the in situ development and similarities to carcinogenesis induction in humans. In this model, CD24 C/¡ and CD24 ¡/¡ mice were treated with 4-NQO (50 mg/mL) in the drinking water for 16 weeks and then changed to regular water for the remainder of the experiment.…”
Section: Low Cd24 Expression In Oral Cancer Is Associated With Poor Pmentioning
confidence: 99%
“…Twenty-four 4-to-6-week-old CBA/CaJ mice received a low-dose (5 mg/mL) tobacco-derivative 4-nitroquinoline 1-oxide (4NQO) painted in their oral cavity (100 mL) 3 times per week for 20 weeks that mimics tobacco-induced carcinogenesis in humans (25), and followed up to 50 weeks. During the same period of carcinogen exposure, mice were also painted 5 times per week with 0, 5, 10, or 15 mg curcumin (in 100 mL of corn oil) to determine if curcumin prevents carcinogenesis.…”
Section: Oral Carcinogen-induced Modelmentioning
confidence: 99%